Efficacy and biomarker analysis of nivolumab plus gemcitabine and cisplatin in patients with unresectable or metastatic biliary tract cancers: results from a phase II study - Yang Liu; Xiang Li; Qian Mei; Weidong Han; Liang Dong; Qingming Yang; Jiejie Liu; Kaichao Feng; Yongtian Zhao; Zhikun Zhao (Journal for ImmunoTherapy of Cancer, 2020)
Background The prognosis of patients with unresectable or metastatic biliary tract cancer (BTC) is unacceptably low. This study aimed to determine the efficacy, safety and predictive biomarkers of the immune checkpoint inhibitor nivolumab in combination with chemotherapy in advanced BTCs.Methods In this open-label, single-arm, phase II trial, a chemotherapy and immunotherapy combination consisting of gemcitabine 1000 mg/m2, cisplatin 75 mg/m2 and nivolumab 3 mg/kg was administered every 3 weeks for up to six cycles. Maintenance treatment with gemcitabine plus nivolumab was administered to patients achieving disease control following the combination therapy. The primary outcome was the objective response rate. Secondary outcomes included safety, disease control rate (DCR), progression-free survival (PFS) and overall survival (OS). The exploratory objective was to assess biomarkers for predicting clinical response and prognosis.Results Thirty-two patients with a median age of 60 (range 27–69) years were enrolled. As of September 31, 2019, the median follow-up was 12.8 (95% CI 10.8 to 14.8) months. Twenty-seven response-evaluable patients received a median of 4 (IQR, 3–6) cycles of combination therapy, of whom 15 (55.6%) patients achieved an objective response, including 5 (18.6%) with a complete response (CR), and the DCR was 92.6%. Of the six patients in cohort A who were resistant to gemcitabine-based or cisplatin-based chemotherapy, one achieved CR and one achieved partial response. Thirteen of 21 chemotherapy-naive patients (61.9%) in cohort B achieved an objective response. The median PFS of all patients in cohorts A+B was 6.1 months. The median OS was 8.5 months, with a 33.3% 12-month OS rate. The most frequent grade 3 or higher adverse events were thrombocytopenia (56%) and neutropenia (22%). Fitness might be a biomarker for predicting clinical response. On-therapy changes in serum soluble FasL, MCP-1 and interferon-γ were correlated with prognosis.Conclusions Nivolumab in combination with gemcitabine and cisplatin offers promising efficacy and a manageable safety profile for patients with advanced BTCs.Trial registration number NCT03311789